Comparison of microwave absorption characteristics of Co-Zr substituted Ni-Zn ferrites and Mg-Zr substituted Ni-Zn ferrites in Ka band (26.5 – 40 GHz). (2022) - Aggarwal, Neha; Narang, Sukhleen Bindra
Abstract: In the present work, microwave absorption characteristics of cobalt-zirconium (Co-Zr) doped and magnesium-zirconium (Mg-Zr) doped nickel zinc (Ni-Zn) ferrites in Ka band, have been compared. The samples with chemical composition, Ni0.6 Zn0.4 (CoZr)x Fe2-2x O4 (x = 0.05, 0.10, 0.15, 0.20 and 0.25) and Ni0.6 Zn0.4 (MgZr)x Fe2-2x O4 (x = 0.05, 0.10, 0.15 and 0.20) have been prepared by sol–gel citrate precursor route and then, sintered at 1000 °C. The absorption characterization has been done by using vector network analyser (VNA) for both the series. Enhancement of dielectric and magnetic properties is observed with the addition of Co-Zr & Mg-Zr in simple Ni-Zn spinel ferrites, which make these ferrites suitable to work as microwave absorber materials (MAMs) in high frequency shielding applications. The minimum values of reflection loss (RL) obtained in both the series have been compared and it has been found that Mg-Zr substituted Ni-Zn ferrites (with lowest RL equal to −53.19 dB) perform better in terms of absorption than their counterpart Co-Zr doped Ni-Zn ferrites (with lowest RL equal to –33.06 dB). The prepared compositions of both the series, can be effectively used as high-performance microwave absorbers.